Evidencing Excellent Thermal‐ and Photostability for Single‐Component Organic Solar Cells with Inherently Built‐In Microstructure. Issue 21 (8th April 2019) - He, Yakun; Heumüller, Thomas; Lai, Wenbin; Feng, Guitao; Classen, Andrej; Du, Xiaoyan; Liu, Chao; Li, Weiwei; Li, Ning; Brabec, Christoph J.
Abstract: Solution‐processed organic solar cells (OSCs) are promising low‐cost, flexible, portable renewable sources for future energy supply. The state‐of‐the‐art OSCs are typically fabricated from a bulk‐heterojunction (BHJ) active layer containing well‐mixed donor and acceptor molecules in the nanometer regime. However, BHJ solar cells suffer from stability problems caused by the severe morphological changes upon thermal or illumination stress. In comparison, single‐component organic solar cells (SCOSCs) based on a double‐cable conjugated polymer with a covalently stabilized microstructure is suggested to be a key strategy for superior long‐term stability. Here, the thermal‐ and photostability of SCOSCs based on a model double‐cable polymer is systematically investigated. It is encouraging to find that under 90 °C & 1 sun illumination, the performance of SCOSCs remains substantially stable. Transport measurements show that charge generation and recombination (lifetime and recombination order) hardly change during the aging process. Particularly, the SCOSCs exhibit ultrahigh long‐term thermal stability with 100% PCE remaining after heating at temperature up to 160 °C for over 400 h, indicating an excellent candidate for extremely rugged applications. Abstract : Development of single‐component organic solar cells employing a conjugated double‐cable polymer is an elegant strategy to overcome the microstructure instability of typical bulk‐heterojunction organic solar cells. This communication demonstrates that single‐component solar cells can exhibit excellent thermal‐ and photostability under harsh conditions, such as 90 °C & 1 sun illumination, and retain 100% performance at 160 °C for over 400 h.